2016
DOI: 10.11591/edulearn.v10i2.3238
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Service Quality toward Open University Website on The Level of Student Satisfaction

Abstract: The purpose of this research is to find out the impact of variable service usability, information quality, and service interaction quality to students' satisfaction in applying open-university website. The population is nonprimary education students on two district areas, that is, West Ceram and Southeast Moluccas including thirty (30) respondents. This research uses purposive sampling as research method in which it fulfils total of thirty (30) respondents. The questionnaire was tested by using reliability tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…When users feel they do not get the information they need easily, they turn to another website ( 19 ). A study conducted by Sahusilawane et al, reported that in some cases they had easier access to their needed information via oral communication or by consulting other students than they could get from websites ( 20 ). It seems that if the university health department website had a better information structure, it would probably determine the effectiveness of users in finding health information.…”
Section: Discussionmentioning
confidence: 99%
“…When users feel they do not get the information they need easily, they turn to another website ( 19 ). A study conducted by Sahusilawane et al, reported that in some cases they had easier access to their needed information via oral communication or by consulting other students than they could get from websites ( 20 ). It seems that if the university health department website had a better information structure, it would probably determine the effectiveness of users in finding health information.…”
Section: Discussionmentioning
confidence: 99%
“…It seems that the existence of evidence-based information on the website in order to provide quality, complete, valuable and accurate information with the aim of empowering students leads them to identify health information and select a health activity for solving a Health Problem for Self-Care ( 19 ). Other studies have also shown that some users did not use the website because the information sources of the websites were unclear ( 20 , 21 ). The results indicate that the proper architecture of the information on the website guides significantly the students to an environment where the needed information is easily accessible ( 21 ); in that environment the students correctly perceive health information and properly assess health services.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also shown that some users did not use the website because the information sources of the websites were unclear ( 20 , 21 ). The results indicate that the proper architecture of the information on the website guides significantly the students to an environment where the needed information is easily accessible ( 21 ); in that environment the students correctly perceive health information and properly assess health services. Finally, students will be more confident in the health website and make informed decisions to solve health and medical problems.…”
Section: Discussionmentioning
confidence: 99%
“…The use and importance of Websites is increasing with the global reach of the Internet. In the open and distance learning (ODL) approach to education, in contrast to conventional or traditional methods, learners and the teachers are geographically separated; and learners must learn independently, using information and communication technology (ICT; Sahusilawane & Hiariey, 2016). The Website of any ODL institution plays an important role in bridging this gap.…”
Section: Introductionmentioning
confidence: 99%